On the chemical mechanisms of interaction of diabetogenic toxic substances with zinc in the pancreas and methods for its prevention - Meyramov, G.G.; Korchin, V.I.; Shaybek, A.S.; Andreewa, A.P.; Zhuzbaeva, G.O.; Meyramova, D.A.; Abdraimova-Meyramova, A.G. (KSU Publ., 2020)
Article presents data оn chemical mechanisms of binding of Zinc in pancreas of animals and human by diabetogenic chelate active chemicals (DZC) that result destruction and death of pancreatic B-cells within a few minutes and of developing of diabetes mellitus. Authors presented and described a few mechanisms for prevention of binding of Zinc in pancreas that result prevention developing of experimental diabetes in 95–100 % of animals. The authors analyze and substantiate in details on the basis of own investigations (1964– 2018), the chemical mechanisms of zinc blocking in cells, which prevents the possibility of their destruction caused by diabetogenic zinc-binding substances, the possibilities of human contact with which have significantly increased over the past decades. According to the results of our own studies and literature data, the chemical mechanisms of the preventive action of derivatives of Dithiocarbamic acid, amino acids — reduced glutathione, cysteine and histidine, as well as the possibility of chemical neutralization of the blood of the DCS before they reach the pancreas, were investigated.
Диабетогенді уытты заттардың ұйқы безінің мырышымен өзара әрекеттесуінің химиялық механизмдері және оның алдын алу әдістері
Химические механизмы взаимодействия диабетогенных токсических веществ с цинком поджелудочной железы и методы его предотвращения
Keywords: zinc; B-сells; Diabetоgeniс zinс binding сhemiсals; Glutathiоne; Diphenylthiосarbazоne (Dithizоn)